Ethnomedicinal use, phytochemistry and biological activity of the Andean plant Buddleja incana Ruiz & Pav. (Scrophulariaceae) - Enciso, Javier; Amiel, Jose; Miranda, Victor; Mayanga, Ana; Tapia, Salyoc; Fabian, Fredy (Ethnobotany Research and Applications, 2020)
Background: Buddleja incana Ruiz & Pav. (Scrophulariaceae) is an ancestral medicinal plant from the Andes of South America used in traditional medicine since the Inca culture, but currently little studied in its chemical components. The objective of this review is to gather all the scientific information on this plant for the purpose of its use in alternative medicine and at the same time stimulate its study in research groups in the Andean countries. Materials and methods: Various electronic search engines and specialized reference tools such as Google, Google Scholar, Scopus, Web of Science, publication sites and electronic databases (Pubmed, Springer, Wiley and Science Direct) were used. Results: Phytochemical studies have found the following chemical components: flavonoids, steroids, saponins, leucoanthocyanidins, triterpenes, phenols, tannins, reducing sugars, coumarins, alkaloids, terpenes and verbascosides. This plant is used to treat various diseases and pathological conditions, having shown anti-inflammatory, antineoplastic, antispasmodic, antibacterial, antifungal and febrifuge effects, in the following conditions: wounds, neuralgia, skin and gastrointestinal ulcers, papillomatosis, skin cancer, photosensitization, immunomodulator. Conclusions: Buddleja incana was a sacred and medicinal plant of the Incas. It is currently used for the treatment of liver, bronchial and urogenital diseases. It has diuretic, anti-inflammatory, analgesic, antirheumatic, antimicrobial, anti-hyperglycemic, wound regenerating effects, for the treatment of warts, skin ulcers, antiproliferative, and for its photoprotective effect on the skin. In veterinary medicine it is used to treat skin photosensitization in sheep, in bovine warts and in canine oral papillomatosis. Keywords: Buddleja incana, phytochemistry, medicinal plants, flora of the Andes.